The regulation and function of the ESAT-6 gene cluster operons of Mycobacterium tuberculosis - Botha, Jeanine (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScMed (Biomedical Sciences. Molecular Biology and Human Genetics))--University of Stellenbosch, 2006.